Mesozoic–Cenozoic Uplift/Exhumation History of the Qilian Shan, NE Tibetan Plateau: Constraints From Low-Temperature Thermochronology - Chen, Lihao; Song, Chunhui; Wang, Yadong; Fang, Xiaomin; Zhang, Yihu; Zhang, Jing; Chen, Yongfa; He, Pengju (Frontiers in Earth Science, 2021)
The Qilian Shan, which is located along the northeastern margin of the Tibetan Plateau, plays a key role in understanding the dynamics of the outward and upward growth of the plateau. However, when and how tectonic deformation evolved into the geographic pattern currently observed in the Qilian Shan are still ambiguous. Here, apatite fission track (AFT) thermochronology and sedimentology were conducted to interpret the low-temperature tectonic deformation/exhumation events in well-dated late Miocene synorogenic sediment sequences in the Xining Basin, which is adjacent to the southern flank of the Qilian Shan. These new low-temperature thermochronological results suggest that the Qilian Shan experienced four stages of tectonic exhumation during the late Mesozoic-Cenozoic. The Late Cretaceous exhumation events in the Qilian Shan were caused by the diachronous Mesozoic convergence of the Asian Plate and Lhasa Block. In the early Cenozoic (ca. 68-48 Ma), the Qilian Shan quasi-synchronously responded to the Indian-Asian Plate collision. Subsequently, the mountain range experienced two-phase deformation during the Eocene-early Miocene due to the distal eﬀects of ongoing India-Asia Plate convergence. At ca. 8±1 Ma, the Qilian Shan underwent dramatic geomorphological deformation, which marked a change in subsidence along the northeastern margin of the Tibetan Plateau at that time. Our findings suggest that the paleogeographic pattern in the northeastern Tibetan Plateau was affected by the pervasive suture zones in the entire Qilian Shan, in which the pre-Cenozoic and Indian-Asian plate motions reactivated transpressional faults strongly modulated multiperiodic tectonic deformation in northern Tibet during the Cenozoic. These observations provide new evidence for understanding the dynamic mechanisms of the uplift and expansion of the Tibetan Plateau.